Penggunaan LKPD Berbasis Keterampilan Proses Dasar Sains Dengan Model Pembelajaran Problem Solving Untuk Meningkatkan Penguasaan Materi Pemantulan Cahaya - Pulu, Halima; Huliselan, Estevanus Kristian; Esomar, Ketarina (Pattimura University, 2022)
This study aims to determine the increase in mastery of light reflection material in class VIII SMP Negeri 27 Maluku Tengah taught using student worksheets (LKPD) based on basic science process skills (KPDS) with a problem-solving learning model. This type of research is descriptive research with a one-group pretest-posttest research design, with 23 students as research samples obtained using the Random Sampling technique. This research data was collected through written tests and then analyzed descriptively. The results showed that the initial mastery of students was in the failed qualification with an average score of 3.5, and the average final mastery of students was 82.4, which was in good qualification, while the average score of students' cognitive ability achievement based on LKPD was 79.1. This is evidenced by the results of the N-gain test, which shows that the increase in students' mastery of the material is 0.8 in high qualifications. Thus, using KPDS-based LKPD with a problem-solving learning model can improve mastery of light reflection.